Cre-Lox Neurogenetics: 20 Years of Versatile Applications in Brain Research and Counting… - Tsien, Joe Z. (Frontiers in Genetics, 2016)
Defining and manipulating specific neurons in the brain have garnered enormous interest in recent years, because such an approach is now recognized as crucial for deepening our understanding of how the brain works. When I started out to explore the Cre-loxP recombination for brain research in early 1990s, it was written off as a dead-end project by a young fool. Yet over the past 20 years, Cre-lox recombination-mediated neurogenetics has emerged as one of the most powerful and versatile technology platforms for cell-specific gene knockouts, transgenic overexpression, Brainbow imaging, neural pathway tracing with retrovirus and CLARITY, chemical genetics, and optogenetics. Its popularity and greater utility in neuroscience research is also largely thanks to the NIH’s bold Blueprint for Neuroscience Research Initiative to launch several Cre-driver resource projects, as well as individual laboratories and private research organizations. With newly-discovered, genetically-encoded molecules that are capable of responding to sonar and magnetic stimulation, for sonogenetics or magnetogenetics, respectively, or detecting rapid voltage changes in neurons, Cre-lox neurogenetics will continue to aid brain research for years to come.